The rule of peshat : Jewish constructions of the plain sense of scripture in their Christian and Muslim contexts, 900-1270 - Cohen, Mordechai Z. (Philadelphia : University of Pennsylvania Press, 2020)
This book looks at the peshat mode of reading the Bible (as opposed to the midrashic mode). The mode was present in the tenth to twelfth centuries. Peshat is the plain meaning of the text, the plain reading, the philological reading, the nonmystical reading. Our author explores how the peshat mode influenced Christian and Muslim schools of interpretation and vice versa; and how the peshat scholars broke from the midrashic mode of biblical interpretation. Spain, France, and the Middle East were important centers for the peshat mode"--
Introduction -- 1. Geonim and Karaites : appropriating methods of Qur'an interpretation -- 2. The Andalusian School : linguistic and literary advances in the Muslim orbit -- 3. Rashi : Peshat revolution in Northern France -- 4. Qara and Rashbam : refining the Northern French Peshat model -- 5. The Byzantine tradition : a newly discovered exegetical school -- 6. Abraham Ibn Ezra : transplanted Andalusian Peshat model -- 7. Maimonides : Peshat as the basis of Halakhah -- 8. Nahmanides : a new model of scriptural multivalence.
Description based upon print version of record.
Includes bibliographical references and indexes.
JSTOR
Keywords: Bible. -- Criticism, interpretation, etc., Jewish -- History -- To 1500.; Bible. -- Criticism, interpretation, etc. -- History -- To 1500.; Bible. -- Islamic interpretations -- History -- To 1500.; Bible. -- Commentaries -- Early works to 1800.; Bible; RELIGION / Biblical Criticism & Interpretation / Old Testament; Islamic interpretations of sacred works; To 1500; Criticism, interpretation, etc; Early works; History